THE HYPOTHETICAL VIEW: ROLE OF MEDIA IN SNEHA PAKA - Goyal, Manisha; Prajapati, P K (Innoriginal: International Journal of Sciences, 2015)
Sneha kalpana is one of the best dosage forms of ayurveda pharmaceutics in practice from vedic period in different forms. Sneha kalpana provides an idea that sneha kalpas are superior to other dosage forms due to its wider advantages like increased absorption, bioavailability and extraction of fat soluble as well as water soluble active principle at a time in a single formulation. In case of sneha paka, the drava dravyas (media) play an important role. These are facilitating to transfer of the active principles from the solid (kalka dravyas) and later enrich the fluid (sneha) by shifting the active principles. In this review paper attempt will be made to establish probable pharmacodynamics during sneha paka by ayurvedic as well as modern methodology. Key words : sneha, liquid media, mass transfer, solvent etc.